Impact of restrictive red blood cell transfusion strategy on thrombosis‐related events: A meta‐analysis and systematic review. Issue 7 (25th March 2022) - Maimaitiming, Mairehaba; Zhang, Chenxiao; Xie, Jingui; Zheng, Zhichao; Luo, Haidong; Ooi, Oon Cheong
Abstract: Background and Objectives: There is an ongoing controversy regarding the risks of restrictive and liberal red blood cell (RBC) transfusion strategies. This meta‐analysis assessed whether transfusion at a lower threshold was superior to transfusion at a higher threshold, with regard to thrombosis‐related events, that is, whether these outcomes can benefit from a restrictive transfusion strategy is debated. Materials and Methods: We searched PubMed, Cochrane Central Register of Controlled Trials and Scopus from inception up to 31 July 2021. We included randomized controlled trials (RCTs) in any clinical setting that evaluated the effects of restrictive versus liberal RBC transfusion in adults. We used random‐effects models to calculate the risk ratios (RRs) and 95% confidence intervals (CIs) based on pooled data. Results: Thirty RCTs involving 17, 334 participants were included. The pooled RR for thromboembolic events was 0.65 (95% CI 0.44–0.94; p = 0.020; I 2 = 0.0%, very low‐quality evidence), favouring the restrictive strategy. There were no significant differences in cerebrovascular accidents (RR = 0.83; 95% CI 0.64–1.09; p = 0.180; I 2 = 0.0%, very low‐quality evidence) or myocardial infarction (RR = 1.05; 95% CI 0.87–1.26; p = 0.620; I 2 = 0.0%, low‐quality evidence). Subgroup analyses showed that a restrictive (relative to liberal) strategy reduced (1) thromboembolic events in RCTs conducted in North America and (2) myocardial infarctions in the subgroup of RCTs where the restrictive transfusion threshold was 7 g/dl but not in the 8 g/dl subgroup (with a liberal transfusion threshold of 10 g/dl in both subgroups). Conclusions: A restrictive (relative to liberal) transfusion strategy may be effective in reducing venous thrombosis but not arterial thrombosis.